(untitled) (Journal of Libya for geographical studies, 2022)
This study dealt with an important region in the Libyan state, the Gulf of Sirte region, which was described in the past as a geographical separation area between the regions of the historical state. The application of some statistical measures and the theory of accessibility and communication, and the aim of the study is to know the political history of Libya among the historical regions of the Libyan state since the early ages, an attempt to know the factors that helped the Gulf of Sirte to be a geographical link area to Libya and its regions after it was otherwise, and the study concluded that the Gulf of Sirte It is a distinguished location, not in Libya, but in the whole of the Mediterranean basin, and that it is the beating heart of the Libyan state because most of the natural resources have impacted it, and that the population has developed in it from about fifty thousand to nearly half a million people during sixty years, and that the Gulf has a good conductive advantage, as it is easy to reach and connect with from all The Libyan regions, and the study recommends promoting development in the Gulf to further link the two wings of the state. It also recommends transferring the state’s administrative center to it in order to strengthen national unity. Libyan intention.